An Analysis of Students’ Error In Pronouncing English Vowel To Students Of Pharmacy In Stikes Muhammadiyah Lhokseumawe In Academic Year 2024/2025 - Nasir, Muhammad (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2024)
This research was conducted where to analysis of student error in pronouncing English vowel from students of Pharmacy in STIKes Muhammadiyah Lhokseumawe. Most of the students might have problems to pronounce English vowel, although they get an English subject in their campus and they could not mastered the English pronunciation well. This method in this research used was qualitative using descriptive statistic data. The instrument in this research used was test, two random sampling from two class, class A and B where totally 20 students. The finding and discussion this research of analysis students error showed that the students was considered “ Good” in English pronunciation especially in English vowel. The total percentage of error was made by the students is 23.33%. there were divided seven types of dominant errors. There were vowel [i:] (5.31%), vowel [?] (5.22%), vowel [?] (4.73%), vowel [u] (4.05%), vowel [?:] (3.42%), vowel [_] (4.42%), and vowel [I] (1.05%). Based on the findings, it showed that error was made by the students in English vowel was low, it has improved the students considered “Good” in English vowel. keywords: pronunciation, English vowel